From Protest to Parliamentary Coup: An Overview of Brazil's Recent History. Issue 4 (1st October 2016) - Santos, Fabiano; Guarnieri, Fernando
Abstract : Brazil's parliamentary coup has managed to topple the elected PT government with remarkable ease, meeting with little resistance at home or abroad despite the blatant violation of constitutional norms and the almost farcically corrupt record of the new incumbents. How has the neo-right been able to transfer its script of juridical-mediatic manipulation of electoral democracy, previously rehearsed on smaller stages such as Honduras and Paraguay, to the regional hegemon? What are the stakes and perspectives for Brazil's political institutions, and are there any possibilities left for emancipatory movements? Two leading political scientists from Rio de Janeiro chronicle the events so far.